2015
DOI: 10.4136/ambi-agua.1633
|View full text |Cite
|
Sign up to set email alerts
|

Biomass reduction of Salvinia molesta exposed to copper sulfate pentahydrate (CuSO4.5H2O)

Abstract: Copper in the aquatic ecosystem may remain adsorbed or be incorporated into the biomass and undergo biomagnification causing unwanted effects to aquatic macrophyte communities. This study evaluated the biomass reduction of Salvinia molesta (Mitchell) exposed to copper sulphate pentahydrate (CuSO 4 .5H 2 O) under laboratory conditions. Approximately 20.5 g of fresh mass (FM) of S. molesta (0.74 g dry matter, DM) were placed in glass tanks with different concentrations (n = 3) of CuSO 4 .5H 2 O as follows: 0.0; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The greater accumulation of copper ions by the roots of S. natans was expected considering that this plant is classified as a floating free macrophyte and its root system maintains direct contact with the ions of metals dissolved in the water and have, in general, a larger area of abortion than the leaves (Barros & Henares, 2015). In the study with leaves, stems and roots of Potamogeton pectinatus L. exposed to different concentrations of Cu, it was observed that in all treatments in the root biomass there was a higher concentration of the metal (Costa et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The greater accumulation of copper ions by the roots of S. natans was expected considering that this plant is classified as a floating free macrophyte and its root system maintains direct contact with the ions of metals dissolved in the water and have, in general, a larger area of abortion than the leaves (Barros & Henares, 2015). In the study with leaves, stems and roots of Potamogeton pectinatus L. exposed to different concentrations of Cu, it was observed that in all treatments in the root biomass there was a higher concentration of the metal (Costa et al, 2018).…”
Section: Resultsmentioning
confidence: 99%